A Compact Extreme Scattering Event Cloud toward AO 0235+164 - Senkbeil, C.; Ellingsen, S.; Lovell, J.; Macquart, Jean-pierre; Cimo, G.; Jauncey, D. (The American Astronomical Society, 2008)
We present observations of a rare, rapid, high-amplitude extreme scattering event toward the compact BL Lac object AO 0235+164 at 6.65 GHz. The ESE cloud is compact; we estimate its diameter between 0.09 and 0.9 AU, with a distance of less than 3.6 kpc. Limits on the angular extent of the ESE cloud imply a minimum cloud electron density of ~4 x 10 3 cm -3. Based on the amplitude and timescale of the ESE observed here, we suggest that at least one of the transients reported by Bower et al. may be attributed to ESEs.